Fecal and vaginal microbiota of vaccinated and non-vaccinated pregnant elk challenged with Brucella abortus - Tibbs-Cortes, Bienvenido W.; Rahic-Seggerman, Faith M.; Schmitz-Esser, Stephan; Boggiatto, Paola M.; Olsen, Steven; Putz, Ellie J. (Frontiers in Veterinary Science, 2024)
Introduction Brucella abortus is the causative agent of brucellosis in cattle and in humans, resulting in economic losses in the agricultural sector and representing a major threat to public health. Elk populations in the American Northwest are reservoirs for this bacterium and transmit the agent to domestic cattle herds. One potential strategy to mitigate the transmission of brucellosis by elk is vaccination of elk populations against B. abortus; however, elk appear to be immunologically distinct from cattle in their responses to current vaccination strategies. The differences in host response to B. abortus between cattle and elk could be attributed to differences between the cattle and elk innate and adaptive immune responses. Because species-specific interactions between the host microbiome and the immune system are also known to affect immunity, we sought to investigate interactions between the elk microbiome and B. abortus infection and vaccination. Methods We analyzed the fecal and vaginal microbial communities of B. abortus-vaccinated and unvaccinated elk which were challenged with B. abortus during the periparturient period. Results We observed that the elk fecal and vaginal microbiota are similar to those of other ruminants, and these microbial communities were affected both by time of sampling and by vaccination status. Notably, we observed that taxa representing ruminant reproductive tract pathogens tended to increase in abundance in the elk vaginal microbiome following parturition. Furthermore, many of these taxa differed significantly in abundance depending on vaccination status, indicating that vaccination against B. abortus affects the elk vaginal microbiota with potential implications for animal reproductive health. Discussion This study is the first to analyze the vaginal microbiota of any species of the genus Cervus and is also the first to assess the effects of B. abortus vaccination and challenge on the vaginal microbiome.